Why do sleep disorders belong to mental disorder classifications? A network analysis of the "Sleep-Wake Disorders" section of the DSM-5. (October 2021) - Gauld, Christophe; Lopez, Régis; Morin, Charles M.; Maquet, Julien; Mcgonigal, Aileen; Geoffroy, Pierre-Alexis; Fakra, Eric; Philip, Pierre; Dumas, Guillaume; Micoulaud-Franchi, Jean-Arthur
Abstract: This article proposes to investigate how Sleep disorders have been conceptualized within the DSM-5 through symptom network analysis of the diagnostic criteria of the "Sleep-Wake Disorders" section in the DSM-5. We hypothesize that the analysis of the most central symptoms will allow us to better analyze the position of Sleep disorders in Mental disorders. We thus i) extracted the symptoms of the DSM-5 diagnostic criteria of Sleep-Wake disorders, ii) built the Sleep-Wake disorder DSM-5 network representation, and iii) quantified its structure at local and global levels using classical symptom network analysis. Thirty-four different symptoms were identified among the 53 DSM-5 diagnostic criteria of the 9 main disorders of the "Sleep-Wake Disorders" section. The symptom network structure of this section showed that the most central sleep symptoms are "Daytime Sleepiness", the Insomnia symptoms group ("Insomnia initiating", "Insomnia maintaining" and "Non-restorative sleep"), and Behavioral sleep symptoms (such as "Altered oniric activity", "Ambulation", "Abnormal responsiveness"). This network analysis shown that the belonging of Sleep-Wake disorders in the DSM-5 have been associated with central sleep symptoms considered as "Mental", given their phenomenality (qualitative nature of the experience) and subjectivity (in personal mental lives). Such a symptom network analysis can serve as an organizing framework to better understand the complexity of Sleep-Wake disorders by promoting research to connect the architecture of the symptom network to relevant biological, psychological and sociocultural factors. Highlights: The implications for the characterization of sleep disorders are fundamental for nosology and in terms of medicalization. The question of whether sleep disorders are mental disorders remains unresolved. Network analysis provides a robust and innovative methodology to study symptomatology. The most central symptoms of the Sleep-Wake disorders section of the DSM-5 classification are mental symptoms.